Validation of parental reports of rotavirus vaccination of their children compared to the national immunization registry. Issue 21 (9th May 2019) - Bercovich, Shayel; Anis, Emilia; Kassem, Eias; Rubinstein, Uri; Ephros, Moshe; Cohen, Dani; Muhsen, Khitam
Abstract: Background: The introduction of rotavirus vaccines into national immunization programs necessitates vaccine effectiveness evaluations. Parental report of vaccination status is a simple and accessible source of information; however, its validity is unclear. Aims: To validate parental reports of rotavirus immunization compared to documentation of vaccination in national immunization registry, and to assess vaccine effectiveness by each method. Methods: Parents of 1272 children aged 2–59 months from northern Israel hospitalized for gastroenteritis in 2011–2015 were interviewed on the sociodemographics and rotavirus vaccination status of their child. Rotavirus immunization status based on parental report was compared to that documented in the national immunization registry, which was considered the gold standard. Stool samples collected from patients were tested for rotavirus antigen by immunochromotgraphy. In a rotavirus test-negative case-control study, vaccination history was compared between children found positive for rotavirus and those who tested negative. Vaccine effectiveness for ≥ 1 dose vs. zero doses was calculated as: (1-adjusted odds ratio) * 100. Results: The sensitivity and specificity of parental report of their child's immunization with a rotavirus vaccine were 97% (95% CI 96–98), and 75% (95% CI 65–82), respectively. Kappa coefficient was 0.69 (p < 0.001) for the agreement between the two methods. Rotavirus vaccine effectiveness was 72% (95% CI 54–84) when using parental report of rotavirus immunization and 79% (95% CI 62–88) when using the registry. Conclusion: Parental report of their child's immunization with a rotavirus vaccine demonstrated high sensitivity, although the specificity was relatively low. Vaccine effectiveness was similar regardless of method used to determine rotavirus immunization status. Parental report of vaccination status can be useful in vaccine effectiveness assessment.